Prevalence and Determinants of Geohelminthiasis among School-Age Children in Jimma City, Ethiopia - Ahmed Zeynudin; Teshome Degefa; Sultan Suleman; Abdulhakim Abamecha; Zuber Hajikelil; Andreas Wieser (Journal of Tropical Medicine)
School-age children (SAC) are at a higher risk of geohelminth or soil-transmitted helminth (STH) infections due to their practice of walking and playing barefoot, lack of adequate sanitary facilities, and poor personal hygiene. In Ethiopia, periodic deworming has been implemented since 2013 with the aim of interrupting the transmission of STH in children by 2025. To evaluate the likely success of such a control program, it is crucial to monitor the transmission of STH, especially in peri-urban settings where environmental sanitation is modest. The aim of this study was to determine the prevalence and determinants of STH infections among SAC in peri-urban areas of Jimma City, Southwestern Ethiopia. A community-based cross-sectional study was conducted in five peri-urban Kebeles of Jimma City from July to September, 2021. Systematic random sampling was used to select 522 households with at least one child, and 478 children (5–15 years old) were recruited randomly from the households. Data on sociodemographic and potential risk factors were collected using a structured questionnaire. Stool samples from each study participant were collected and examined microscopically using the Kato–Katz technique. Multivariate logistic regression model was used to identify risk factors associated with STH infections. The prevalence of any STH among SAC was 23.4%, with Ascaris lumbricoides being the predominant STH species (15.7%), followed by Trichuris trichiura (9%) and hookworm (2.1%). Most (86.6%) of the STH-positive SAC had a single infection and a light infection intensity (88.2%), with a mean intensity of 367.4 eggs per gram. Location of Kebele (AOR = 2.73; 95% CI: 1.21–6.16, p=0.016), lack of hand washing after defecation (AOR = 6.39; 95% CI: 3.16–12.95, p<0.001), untrimmed fingernails (AOR = 2.65; 95% CI: 1.56–4.51, p<0.001), and lack of previous deworming (AOR = 2.90; 95% CI: 1.47–5.74, p=0.002) were significant predictors for STH infections among SAC. In conclusion, the study revealed that STH infections are significant health problem in the peri-urban areas of Jimma City. Strengthening periodic deworming and improving children’s hygiene through health education are required to reduce the transmission.